Lord Edgware dies - Christie, Agatha (London HarperCollins Publishers, 1954)
Poirot had been present when Jane bragged of her plan to 'get rid' of her estranged husband. Now he is dead and Jane had a cast-iron alibi, she was dining with friends at the time and after all he had granted her a divorce, so what motive did she have?
A Hercule Poirot Mystery.
Keywords: Poirot, Hercule (Fictitious character) -- Private investigators -- England